Design and development of wave energy converter device as a breakwater in coastal area / Muhammad Taufiq A. Rahman, Zaqwan Deraman and Noor Muhamad Fareez Fauzi - A. Rahman, Muhammad Taufiq; Deraman, Zaqwan; Fauzi, Noor Muhamad Fareez (Bahagian Penyelidikan dan Jaringan Industri, UiTM Melaka, 2012)
The erosion in coastal areas may originate from many factors. One of the factors that will lead to erosion is due to human structures having changed the geometry of the coastline. The wave characteristics were changed due to the changes of shore line resulting from the structure nearby shore. Breakwaters constructions are one of the ways to prevent erosion from continuing. From the concepts of breakwater to prevent erosions and at the same time it can produce electricity. By applying wave energy converter concepts which are using oscillating water column and overtopping wave. This design more emphasis on the development of the coastal are wave energy. Through this project, it will be able to provide benefits for the long term because it can act as breakwaters and at the same time can produce electricity.